PROCESSO ORÇAMENTÁRIO E CONFIANÇA SOBRE A APLICAÇÃO DO PRINCÍPIO DA CONTROLABILIDADE EM UMA ORGANIZAÇÃO PÚBLICA - Morais, Mariana Melo de (2020)
This research discusses the concepts of budget planning, control, and the application of the principle of controllability, through the approach of Institutional Theory. The study aims to describe and analyze how institutional factors affect the relationsh